Pharmacogenetics of rheumatoid arthritis: Potential targets from susceptibility genes and present therapies - Darren D O’Rielly; Proton Rahman (Dove Medical Press, 2010)
Darren D O’Rielly, Proton RahmanFaculty of Medicine, Memorial University of Newfoundland, St. John’s, Newfoundland, CanadaAbstract: Rheumatoid arthritis (RA) is a chronic heterogeneous autoimmune disorder of unknown etiology resulting in inflammation in the synovium, cartilage, and bone. Genetic factors play an important role in susceptibility to RA as the heritability of RA is between 50% and 60%, with the human leukocyte antigen (HLA) locus accounting for at least 30% of overall genetic risk. Outside the major histocompatibility complex (MHC) region, six additional risk loci have been identified and validated including PTPN22, STAT4, PADI4, CTLA4, TNFAIP3-OLIG3, and TRAF1/C5. Genetic factors are also important in RA pharmacotherapy due to the gene-dependent activity of enzymes involved in the pharmacokinetics and/or pharmacodynamics of RA medications. Indeed, there is great variability in drug efficacy as well as adverse events associated with any anti-rheumatic therapy and genetics is thought to contribute significantly to this inter-individual variability in response. This review will summarize the genetic factors that have been implicated in the pathogenesis of RA, and how these determinants may factor into the potential pharmacogenetics of this disease. We will also review the therapeutic agents that are currently being utilized or presently being evaluated in the treatment of RA, along with potential pharmacogenetic markers that have been proposed for such medications.Keywords: rheumatoid arthritis, susceptibility genes, pharmacogenetics